EVALUASI HUJAN BERBASIS SATELIT GPM-IMERG DI WILAYAH SUNGAI HALMAHERA UTARA UNTUK PENGELOLAAN SUMBER DAYA AIR - Partarini, Ni Made Candra (Jurnal Teknik Sipil dan Arsitektur, 2025)
Hydrological data is a crucial component in the planning and management of water resources (SDA) in Indonesia. The availability of data to date remains a critical issue that requires immediate attention. Satellite-based rainfall data has emerged as a promising alternative with better spatial and temporal scale coverage. This satellite data has been applied globally, especially for hydrological disaster prediction in various locations. Satellite rainfall technology continues to evolve with improvements in both quality and quantity over time. This research aims to assess the feasibility of using satellite rainfall data released by NASA, known as the Global Precipitation Measurement - Integrated Multi-satellite Retrievals for GPM (GPM-IMERG), for water resources management. The study location is the North Halmahera River Basin (WS). The feasibility assessment is conducted by comparing satellite rainfall data against field observation data represented by rain gauge stations scattered throughout the study area. The satellite performance assessment uses metric evaluation methods, including Probability of Detection (POD), False Alarm Ratio (FAR), Critical Success Index (CSI), and accuracy (fraction correct). The analysis results indicate that GPM-IMERG data demonstrates good performance in predicting rainfall in the South Halmahera River Basin based on the obtained evaluation metric values. Based on the metric evaluation, GPM-IMERG satellite rainfall data at 11 locations shows good performance in predicting rainfall in the North Halmahera River Basin. This is evident from the Probability of Detection (POD) values ranging from 0.90 to 0.99, the False Alarm Ratio (FAR) between 0.41 and 0.80, as well as the Critical Success Index (CSI) meeting values of 0.20 to 0.58, and cccuracy ranging from 0.33 to 0.66.